Bridging the Digital Divide in Healthcare: Insights on Literacy, Empowerment, and Portal Adoption - Alifah, Rafidha Nur (Medicor : Journal of Health Informatics and Health Policy, 2024)
The adoption of digital health portals represents a major shift toward patient-centered care. These portals empower patients by improving access to health information and facilitating communication with providers. This review synthesizes evidence on how portals influence empowerment, with emphasis on digital literacy and health outcomes. Findings show that patients with strong digital skills actively use portals, achieve better chronic disease management, and report higher satisfaction. Quantitative evidence includes a 0.5% reduction in HbA1c and improved blood pressure regulation among users. However, vulnerable populations face persistent barriers such as limited literacy, low socioeconomic status, and inadequate infrastructure. Systemic obstacles like interoperability issues and provider workload also limit portal effectiveness. Policy strategies should focus on digital literacy education, universal internet access, and strong privacy protections to ensure equitable benefits. Future research must adopt longitudinal and inclusive approaches to strengthen evidence and guide equitable implementation